Behavioral Economics and Social Exclusion : Can Interventions Overcome Prejudice? - Hoff, Karla (World Bank Group, Washington, DC, 2015)
Behavioral economics recognizes that mental models -- intuitive sets of ideas about how things work -- can bias an individual's perceptions of himself and the world. By representing an ascriptive category of people as unworthy, a mental model can foster unjust social exclusion of, for example, a race, gender, caste, or class. Since the representation is a social construction, shouldn't society be able to control it? But how? This paper considers three interventions that have had some success in developing countries: (1) Group deliberation in Senegal challenged the traditional mental model of female genital cutting and contributed to the abandonment of the practice; (2) political reservations for women and low castes in India improved the way men perceived women, the way parents perceived their daughters, and the way women perceived themselves, but have not generally had positive effects on the low castes; and (3) reductions in the salience of identity closed performance gaps between dominant and stigmatized groups in experiments in India and China. Spoiled collective identities need to be changed or made less prominent in order to overcome social exclusion.